Peningkatan Kompetensi Guru PAI pada Pelaksanaan Pembelajaran Jarak Jauh (PJJ) di Masa Pandemi Covid-19 - Putra Ulinuha (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
Covid-19 causes learning to be a different pattern, to avoid transmitting the virus. So schools carry out learning using the internet network. Teachers can use applications that match the material. The purpose of the study was to obtain and reveal the efforts of PAI teachers in dealing with teaching and learning activities during the Covid-19 period at SDIT Al Islamiyah Bae Kudus. This research was conducted at SDIT Al Islamiyah Bae Kudus using a qualitative approach. Data was collected through interviews, observation, and documentation. The results of this study, firstly, found that PAI teachers actively participated in online webinars every time there was training from the KKG PAI Kudus Regency and took online webinars held from the Kudus Regency Education Office and participated in training from the Central Java Province KKG. Second, revealing that PAI teachers have realized the importance of technology and applications for learning during the Covid-19 pandemic.